The book of Henry [videorecording (DVD)] - Watts, Naomi, 1968-; Martell, Jaeden; Tremblay, Jacob (Universal Pictures Home Entertainment, 2017)
A single mother discovers a scheme in her son's book to rescue a young girl from the hands of her abusive stepfather and sets out to execute the plan at any cost.